FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN SEBELUM DAN DI MASA PANDEMI COVID-19 - Aurellia, Ivana; Yanti, Yanti (Jurnal Paradigma Akuntansi, 2024)
This study aims to examine the effect of capital structure, liquidity, firm size, and intellectual capital on firm performance in manufacturing companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic, and differences in average firm performance before and during Covid-19 pandemic. The sample was selected by purposive sampling method and use 77 manufacturing companies as sample for 2019 representing pre-pandemic condition and 2020 representing condition during the pandemic. Hypothesis testing with regression analysis and Wilcoxon signed-rank test using IBM SPSS 25 program and Microsoft Excel 2016. Research before and during pandemic shows intellectual capital has significant effect on firm performance and found insignificant differences between average firm performance before and during pandemic. The implication is the need to increase the intellectual capital on resources in the company in order to improve company performance.